Between Nature and Civilization(s): American Wilderness as a Eurocentric Cultural Construct in Tony Morrison’s "A Mercy" - Vysotska, Natalia (Tematy i Konteksty, 2023)
The paper sets out to explore the ways the traditional Western opposition “nature vs. civilization” is reworked in Toni Morrison’s A Mercy. The first aspect addressed in the paper is the author’s recasting of the original Puritan myth of America as New Eden by demonstrating the historical impossibility of human-nature and human-human harmony on the “new” continent. This is achieved through presenting Jacob Vaark’s New England farm as a metaphor of Eden/enclosed garden transmogrifying from Utopian to Dystopian mode of functioning in the text, with apparent ecofeminist overtones.The second issue dealt with is “wilderness” as one of the basic concepts underlying American Puritan world picture. The paper argues that in the novel “wilderness” as an inherent characteristic of England’s transatlantic territorial expanses, including both their physical and human resources, loses its essentialism and is unmasked as a Eurocentric cultural construct. In addition, the novel extends the notion of “civilization” beyond its Eurocentric boundaries featuring two non-European civilizations – Native American and African – as suggesting alternative (and much more positive) models of “nature-civilization” relationship.